The economywide effects of teff, wheat, and maize production increases in Ethiopia: Results of economywide modeling - Benson, Todd; Engida, Ermias; Thurlow, James (International Food Policy Research Institute, 2014)
The government of Ethiopia is investing significant public resources to increase overall national production of teff, wheat, and maize. To better understand the likely economywide effects of increases of between 12 and 14 percent in the national production of these cereals, a set of production increase scenarios for each crop were run using a computable general equilibrium model of the Ethiopian economy. The analyses were extended to also consider the effects of several international wheat price and wheat import scenarios, a wheat subsidy program, and maize exports. Among the effects considered are changes in economic growth, prices, total household consumption, cereal and calorie consumption levels, and poverty measures.